2022
DOI: 10.14430/arctic74372
|View full text |Cite
|
Sign up to set email alerts
|

Inuit Food Insecurity as a Consequence of Fragmented Marine Resource Management Policies? Emerging Lessons from Nunatsiavut

Abstract: Historically, Inuit communities of the Arctic have relied significantly on the living marine resources of their coastal waters for nutrition, underpinning community cohesion and enhancing individual and collective well-being. Inadequate understanding of the conditions of coastal marine stocks and their dynamics, along with failed past fisheries management practices, now threatens secure access to these resources for food and nutrition. We examine the degree of integration of modern Canadian federal food and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…A summary of study characteristics can be found in Table 2 and a detailed overview can be found in the Appendix A Materials. Of the 31 articles included in this review, 39% (12 articles) used qualitative methods [58][59][60][61][62][63][64][65][66][67][68][69], 52% (16 articles) used quantitative methods [11,16,21,34,[59][60][61][62][63][64][65][66][67][68][69][70][71], and 9% (3 articles) used "other" methods [70][71][72]. Specific methods used in the studies included semi-structured interviews (10 articles) [58][59][60][61][64][65][66][67]69,71], cross-sectional surveys (11 articles) [11,16,21,69,[73]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A summary of study characteristics can be found in Table 2 and a detailed overview can be found in the Appendix A Materials. Of the 31 articles included in this review, 39% (12 articles) used qualitative methods [58][59][60][61][62][63][64][65][66][67][68][69], 52% (16 articles) used quantitative methods [11,16,21,34,[59][60][61][62][63][64][65][66][67][68][69][70][71], and 9% (3 articles) used "other" methods [70][71][72]. Specific methods used in the studies included semi-structured interviews (10 articles) [58][59][60][61][64][65][66][67]69,71], cross-sectional surveys (11 articles) [11,16,21,69,[73]…”
Section: Methodsmentioning
confidence: 99%
“…Nunavut was the most studied region (eleven articles) [11,59,61,62,65,67,[69][70][71][72]81], followed by Nunavik (nine articles) [58,63,64,71,[74][75][76][77]79]. One article focused on Nunatsiavut [66]. Eleven studies focused on multiple Arctic regions [21,33,60,73,78,80,[82][83][84][85], both nationally and globally [21,33,60,73,78,80,[82][83][84][85].…”
Section: Geographic Focusmentioning
confidence: 99%
“…Although limitations of conventional economic indicators in capturing dynamics of ICs are well known, alternative metrics are scarce. Food security for example requires a shift beyond affordability measures to encompass various subsistence harvesting dimensions (from households' structure associated to harvest capacity to opportunity costs of wage employment and community catch sharing) [12,13]. Broadening the scope of economic analysis to encompass comprehensive indicators, allows economists to better understand Indigenous needs and values, recognizing sources of value for Arctic ICs, from local resource control to job security and access to marine resources for subsistence harvest [2].…”
Section: Economic Tools and Future Directions In Enhancing Indigenous...mentioning
confidence: 99%
“…Indicators for monitoring performance against social objectives can include employment, work satisfaction, proportion of new entrants, reduced dependence on remittances, social connectivity among communities, equitable distribution of catch value, extent and nature of fisheries‐related cultural and spiritual practices, (mal)nutrition and measures of overcoming vulnerability related to comorbid health conditions under conditions of structural and political adversity (Biedenweg et al, 2016; Durgun et al, 2021; Kourantidou et al, 2021; Kronen et al, 2010; Plagányi et al, 2013; Slagboom et al, 2020; see also Data S2—Fisheries Social Objectives).…”
Section: What Might An Shcr Look Like?mentioning
confidence: 99%